The Ensouled Body: Towards a Phenomenology of the Stratum of Animality (Phenomenology, Humanities and Sciences, 2022)
This article is divided into two parts. In the first, I proceed to a description of the self-giving of ourselves and distinguish two main axes: the sense of separation between body and mind and the sense of mind-body superposition. On the basis of these, I stress the correctness of the distinction between body and mind, but I reject that the distinction can be carried over to the thesis of actual separation and, further, of the supposed independence of mind (the anima) from the body. In the second part, I try to show how the phenomenon of the atopic decentralization of the mind relative to the body, which was described in the first part, is not something intrinsic to the mind, per se, but can be found already in the self-organization of the somatic body, such that even considering the stratum of the “animality” of subjectivity, that is, the somatic dimension of a living, organic body, this decentralization is already present. With this, I show how one can speak of an “animal subjectivity” and what are the phenomena that constitute it, focusing on the axis of bodily self-structuring, which already presents the phenomenon of atopic delocalization I spoke of earlier.
Keywords: Subjectivity; Body; Mind; Animality; Phenomenology